Measurement of the Temperature of Rubidium Atoms in a Magneto-Optical Trap - Liwag, J. W. F.; Sicam, V. A.; Karremans, K. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
We have performed measurements that can be used to determine the temperature of rubidium atoms in a magneto-optical trap. The expansion of the atomic cloud after switching off the current through the anti-Helmholtz coils was recorded with a CCD camera. Analysis of the measurements revealed that the cloud of atoms in optical molasses expands at a velocity of 4 cm/s.